2011
DOI: 10.1073/pnas.1102855108
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal evasion of humoral immunotherapy in aggressive B-cell lymphoma modulated by ATP-binding cassette transporter A3

Abstract: Targeting the surface of malignant cells has evolved into a cornerstone in cancer therapy, paradigmatically introduced by the success of humoral immunotherapy against CD20 in malignant lymphoma. However, tumor cell susceptibility to immunochemotherapy varies, with mostly a fatal outcome in cases of resistant disease. Here, we show that lymphoma exosomes shield target cells from antibody attack and that exosome biogenesis is modulated by the lysosome-related organelle-associated ATP-binding cassette (ABC) trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
252
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(264 citation statements)
references
References 57 publications
10
252
0
2
Order By: Relevance
“…Figure key is shown at the right side. The images in the figures are not scaled lysobisphosphatidic acid (LBPA) are involved in the MVB biogenesis and exosome secretion, although how protein cargoes are selectively transported into this kind of vesicles remains unknown [64][65][66][67][68][69][70][71].…”
Section: Escrt-dependent and Independent Sorting Mechanisms Into Ilvsmentioning
confidence: 99%
“…Figure key is shown at the right side. The images in the figures are not scaled lysobisphosphatidic acid (LBPA) are involved in the MVB biogenesis and exosome secretion, although how protein cargoes are selectively transported into this kind of vesicles remains unknown [64][65][66][67][68][69][70][71].…”
Section: Escrt-dependent and Independent Sorting Mechanisms Into Ilvsmentioning
confidence: 99%
“…[21][22][23][24] Our recent study demonstrated that aggressive lymphoma cells produce ample amounts of exosomes, which are involved in mechanisms of cellular resistance against humoral immunotherapy. 29 In the present study, we applied high amounts of purified exosomes to lymphoma cells in the CFU assay and For personal use only. on May 10, 2018. by guest www.bloodjournal.org From found a significant stimulation of clonogenic growth of lymphoma SP and also, to some degree, non-SP cells ( Figure 6A).…”
Section: Exosome-mediated Transport Of the Wnt3a Proteinmentioning
confidence: 99%
“…26 In normal physiology, exosomes are secreted from erythroid progenitors during progenitor cell maturation, as well as from normal and transformed B lymphocytes and dendritic cells, and possess immunomodulatory functions. [27][28][29] In view of the above and the emerging role of exosomes in the Wnt signaling pathway, the objective of the present study was to identify putative tumor stem cells in aggressive lymphomas of diffuse large B-cell lymphoma (DLBCL) type and investigate the mechanisms by which the formation of SP and non-SP cells are modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report that exosomes from cancer cells attenuate the anti-tumor effects of immunotherapeutic drugs such as rituximab and trastuzumab by acting as a decoy for cancer cells [84,85]. Therefore, cancer researchers are attempting to remove such exosomes from patient blood.…”
Section: Exosome Targeting Therapymentioning
confidence: 99%
“…Ciravolo et al [84] also reported that the exosomes from HER2-positive breast cancer cells display HER2 protein on their surface, thereby competitively inhibiting the interaction between breast cancer cells and trastuzumab, and ultimately leading to tumor cell proliferation and poor prognosis. Aung et al [85] found that lymphoma-derived exosomes that display CD20 protein on their surface inhibit the anti-tumor effects of the anti-CD20 chimeric antibody rituximab by direct binding. These findings suggest that reduction or removal of cancer exosomes would support immunotherapy against cancer-specific antigens.…”
Section: Exosome Targeting Therapymentioning
confidence: 99%